Automated Detection of Acute Lymphoblastic Leukemia From Microscopic Images Based on Human Visual Perception - Bodzas, Alexandra; Kodytek, Pavel; Zidek, Jan (Frontiers in Bioengineering and Biotechnology, 2020)
Microscopic image analysis plays a significant role in initial leukaemia screening and its efficient diagnostics. Since the present conventional methodologies partly rely on manual examination, which is time consuming and depends greatly on the experience of domain experts, automated leukaemia detection opens up new possibilities to minimize human intervention and provide more accurate clinical information. This paper proposes a novel approach based on conventional digital image processing techniques and machine learning algorithms to automatically identify acute lymphoblastic leukaemia from peripheral blood smear images. To overcome the greatest challenges in the segmentation phase, we implemented extensive pre-processing and introduced a three-phase filtration algorithm to achieve the best segmentation results. Moreover, sixteen robust features were extracted from the images in the way that haematological experts do, which significantly increased the capability of the classifiers to recognize leukaemic cells in microscopic images. To perform the classification, we applied two traditional machine learning classifiers, the artificial neural network and the support vector machine. Both methods reached a specificity of 95.31 %, and the sensitivity of the support vector machine and artificial neural network reached 98.25 and 100 %, respectively.